Cultural Literacy in Local Wisdom for Strengthening the Spirit of Mutual Cooperation - Nurur Rubingah; Ali Imron Al Ma'ruf; Harun Joko Prayitno; Irfan Miftahul Fauzi; Gian Sugiana Sugara; Dian Artha Kusumaningtyas (International Conference on Education for All, 2023)
Mutual cooperation is one of the dimensions of the Pancasila Student Profile developed in the independent curriculum. The spirit of mutual cooperation can be nurtured through cultural literacy, utilizing local wisdom, which refers to an individual's ability to comprehend and interact with various cultural aspects in their surroundings, as well as the knowledge, practices, and values associated with the distinctive culture of a specific region or community. This research employs a qualitative method with a phenomenological approach among students at SDN 3 Nanggulan, Cawas District, Klaten Regency. The aim is to describe the strengthening of the spirit of mutual cooperation through cultural literacy within the framework of local wisdom formulated in the Pancasila Student Profile reinforcement project. The findings of this study identify the steps involved in the implementation of the Pancasila Student Profile reinforcement project, including initial identification, theme selection, and execution involving external parties. The implementation of the Pancasila Student Profile reinforcement project with a focus on local wisdom is carried out through the choreography of a new creative dance performance titled "Gotong Royong."